Atrial and atrioventricular resynchronization the benefit of bachmanns bundle and his bundle pacing. (25th November 2020) - Wolff, P; Strozik, P; Gajek, A; Ciesielski, A; Slawuta, A; Gajek, J
Abstract: : The current treatment of patients with heart failure and concomitant atrioventricular conduction delay is difficult. Recommendations indicate the possibility to use the classic resynchronization but in the presence of narrow QRS-complex such approach could be even harmful. Without a sufficient LBBB morphology as indication for classical CRT, those patients would lose their narrow QRS complex with negative consequences for the hearts functional status. A new therapeutic option for those patients to re-establish the physiological atrioventricular mechanical sequence is the permanent His-bundle pacing (pHBP). Advantages like physiological activation sequence of the ventricular myocardium, less affected by AF compared to classical CRT and reversal of mitral regurgitation should be enumerated to show it's beneficial effect. Additionally the use of Bachmann's-bundle pacing can correct the prolonged interatrial conduction thus further contribute to the echocardiographic and clinical improvement. The aim of the study is to assess the influence of Bachmann's-bundle pacing and His-bundle pacing on the reversed remodeling of the heart in patients with heart failure and atrioventricular block. The study group included 21 patients (7 women and 14 men) undergoing cardiac resynchronization using Bachmann's-bundle pacing and permanent His-bundle pacing from LV channel for atrioventricular conduction delay. All the patients had narrow QRS-complex which prevented us to use classic resynchronization. 13 CRT-D and 8 CRT-P devices were implanted according to the ejection fraction and ventricular arrhythmia risk assessment. In all patients the direct His-bundle pacing was successfully achieved, selective in 17 and non-selective in 4 patients. The mean follow-up (FU) period was 8.8 months (1–26 months). The echocardiographic, clinical and ECG results are presented in the table 1. Conclusions: 1. The correction of atrioventricular and interatrial conduction delay resulting in improvement of atrioventricular mechanical coupling can contribute to the reversed remodeling of the heart. 2. This also improves the patient's functional status. 3. In some patients this approach could lead to the normalization of echocardiographic parameters of the left ventricle. Funding Acknowledgement: Type of funding source: None